Exploration augmented reality-based flashcards as a teaching tool to improve children's cognitive ability - Eri Mardiani; Fujiono Fujiono; Citra Siwi Hanayanti; Nana Citrawati Lestari; Trimey Liria Hutauruk (Sean Institute, 2024)
The present study examines the revolutionary capacity of Augmented Reality (AR) by employing AR-based flashcards as an inventive pedagogical instrument to augment the cognitive capacities of young learners. Motivated by an acknowledgment of the constraints inherent in conventional pedagogical techniques, the objective of this study is to establish a connection between established methods and state-of-the-art technologies. The study employed an experimental design, consisting of control and experimental groups, to assess the effects of augmented reality (AR) flashcards on the problem-solving abilities and memory retention of children. Augmented reality significantly improved memory retention by supplying supplementary stimuli throughout the encoding and retrieval processes. In addition, compared to children who utilized conventional flashcards, those who utilized AR-based flashcards demonstrated enhanced critical and analytical reasoning. The results of this study underscore the general efficacy of augmented reality (AR) instructional aids in enhancing cognitive capacities. Consequently, this opens the door for their incorporation into the curriculum of early childhood education. With the continuous evolution of the educational landscape, this study makes a valuable contribution to the ongoing dialogue surrounding the incorporation of augmented reality (AR), underscoring the criticality of developing learning environments that are both adaptive and engaging.